Move, Collaborate, and Iterate: Improving the Work from Home Experience - Haliburton, Luke; Schmidt, Albrecht (2020)
ABSTRACT The coronavirus pandemic has caused a dramatic shift for knowledge workers around the world. People are working remotely from their homes for an extended period of time, causing several significant issues for well-being and productivity. In this position paper, we address the issues of reduced physical activity, spontaneous synchronous interactions, and feedback on work. For many workers, being confined to their home has eliminated much of the physical activity that was previously built into their day. To address this, we discuss technologies to support working on the move. Although video conferencing has served as an adequate replacement for in-person meetings, workers are missing the spontaneous and informal interactions that lead to diffuse thinking and novel ideas. Isolation at home also leads to a lack of feedback on work progress and accomplishments. We discuss technology-based solutions to tackle these issues, which can be applied to any remote working scenario. Keywords human-centered design, healthy workplaces, well-being, collaboration, COVID-19, home office https://youtu.be/fjsuOjwnATI ABOUT THE AUTHOR/S Luke Haliburton LMU Munich luke.haliburton@ifi.lmu.de Luke Haliburton is a PhD student in Human Computer Interaction at LMU in Munich, Germany. His research focuses on the effects of digital technology on user health, particularly through the lenses of digital stress and human-centered design. Luke uses design as a research tool to develop technologies for healthy workplaces To learn more please refer to his personal website: https://lukehaliburton.com/ Albrecht Schmidt LMU Munich albrecht.schmidt@ifi.lmu.de New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).